An antifungal body soap from stem bark of Entada spiralis Ridl.(Akar Sintok) as a new cosmeticeutical product - Mat So'ad, Siti Zaiton; Harun, Aiza; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini; Abdullah, Jariah (Research, Industrial Linkage Industry, Community& Alumni Network Division, UiTM Pulau Pinang, 2013)
The stem bark of Entada spiralis Ridl. locally known as “sintok” has been used traditionally for generations as washing agent, syampoo and body soap. The formation of foam when stem bark agitated in water gave indication of the presence of saponin. The phytochemical investigations of methanolic extract and its fraction discovered saponins and terpenoids as active components since they were responsible for the inhibitory effect against some fungal which can cause skin infection such as Trichophyton mentagrophytes, Trychophyton tonsurans and Microsporum gypseum. Throughout this finding, we found the stem bark exhibited potential for the development of skin care product such as body soap. Thus, a body soap product has been designed from stem bark of E. spiralis and this product demonstrated very good results from most of the consumers. This saponin content-body soap product from E. spiralis stem bark has been formulated for the first time to treat skin problems and is hoped to build better health care system in future.